Exploring Major Stressors and Coping Dimensions of Zimbabwean University Female Students: A Qualitative Study - Moyo A. (Research and Scientific Innovation Society, 2022)
The study investigated stress and coping mechanisms amongst female university students in Zimbabwe. Many female students in universities have to handle various stressors caused by personal, academic, social, and sometimes work lives. Students with inadequate stress handling skills can face difficulties in trying to balance these responsibilities. The study was aimed at assessing stress and stressors amongst the female students, and also the coping strategies that can be used to handle stress. Female university students from the Midlands State University were interviewed as the respondents of this study, and the data received was qualitatively assessed to determine the stressors, stress levels, and coping mechanisms. Overall, the students indicated that the key stressors they experienced were disadvantaged social backgrounds, menstruation and menstrual disorders, sexual harassment, information overload, peer competition, transition from adolescence to adulthood, personal inadequacy, and lecturer- student relationships. It was observed that the students apply four main coping strategies namely venting, instrumental support, emotional support, and self-distraction. The study concluded by recommending that additional studies are warranted to look into reduction of student stress for both genders and developing coping mechanisms.